IMMU-06. COMBINATORIAL IMMUNE CHECKPOINT INHIBITORS FOR TARGETED INTRATUMORAL DELIVERY IN GBM. (12th November 2021) - Sanders, Stephanie; Herpai, Denise; Debinski, Waldemar
Abstract: Glioblastoma (GBM) is an immunologically cold tumor. Using single cell sequencing of CD45 + cells we confirmed that T cells are present within GBM samples. These T cells are positive for exhaustion markers such as LAG3 and TIGIT, as well as CTLA4 and PD1 checkpoint receptors. Modulating T cell activity through use of immune checkpoint inhibitors (ICIs) has shown efficacy in the treatment of a variety of solid tumors, and the combination of anti-CTLA4 and anti-PD1 ICIs has shown increased efficacy over use of a single therapeutic. Additionally, targeting ICIs to the tumor cells may increase efficacy of this treatment. We therefore constructed a combinatorial ICI redirected to GBM via interleukin 13 receptor alpha 2 (IL13RA2), a receptor over-expressed on the majority of GBM cells but not normal brain. The first component of the construct, labeled with a histidine tag, targets CTLA4 while the second component, tagged with a StrepII tag, targets PD1. The tags added to the constructs will allow for purification of a combinatorial heterodimer simultaneously targeting PD1, CTLA4 and IL13RA2. We purified individual components via fast protein liquid chromatography (FPLC) using a proteinG column followed by a HisTrap or StrepTrap column. We obtained a recombinant, targeted multivalent ICI at > 95% purity. We found that these constructs are able to bind their target receptors via ELISA in which the Kd values ranged from picomolar to low nanomolar range. Additionally, our constructs bind their target on live cells by flow cytometry. We next designed a heterodimeric construct which can combinatorially target CTLA4 and PD1 while also directing the ICI therapy to GBM. These constructs in conjunction with other immune stimulants like cytotoxic therapies are intended to facilitate the interaction between T cells and GBM tumor cells directly in a tumor microenvironment.